Studies and sport at the University - problems and benefits of sport at University Club - Kajetan Suchecki (Nicolaus Copernicus University in Toruń, 2016)
University Sports Association is one of the most active student organizations in Poland. Most members of the AZS are students who, between the duties of studying, do sports and represent their universities on academic competitions. Sport during the studies required to mobilize the time between the obligations related to learning which is not always easy.                 This paper is based on the analysis of an available literature and a research conducted through a questionnaire survey among active members of the  AZS University Club at the University of Economics in Katowice. The aim of this article is to answer the question as sports in the Club and activities in AZS effect on school results and developing skills of students.                 In the conclusions we presented different effects of sport on academic results, referring both to the amount of time devoted to learning, as well as its quality.